Sex-differential RXRα gene methylation effects on mRNA and protein expression in umbilical cord of the offspring rat exposed to maternal obesity - Chavira-Suárez, Erika; Reyes-Castro, Luis Antonio; López-Tenorio, Itzel Ivonn; Vargas-Hernández, Lilia; Rodríguez-González, Guadalupe L.; Chavira, Roberto; Zárate-Segura, Paola; Domínguez-López, Aaron; Vadillo-Ortega, Felipe; Zambrano, Elena (Frontiers in Cell and Developmental Biology, 2022)
Maternal obesity (MO) induces negative consequences in the offspring development. Adiposity phenotype is associated with maternal diet at early pregnancy and DNA methylation marks in the RXRα promotor at birth. Glucocorticoids play an important role in the regulation of metabolism through the activation of nuclear hormone receptors such as the RXRα protein. The aim of the study was to analyze steroid hormone changes at the end of pregnancy in the obese mother and RXRα gene methylation in the umbilical cord. For this purpose, in a well-established MO model, female Wistar rats were fed either standard chow (controls: C) or high-fat obesogenic diet (MO) before and during pregnancy to evaluate at 19 days of gestation (19 dG): 1) maternal concentration of circulating steroid hormones in MO and C groups, 2) maternal and fetal weights, 3) analysis of correlation between hormones concentration and maternal and fetal weights, 4) DNA methylation status of a single locus of RXRα gene near the early growth response (EGR-1) protein DNA binding site, and 5) RXRα mRNA and protein expressions in umbilical cords. Our results demonstrate that at 19 dG, MO body weight before and during pregnancy was higher than C; MO progesterone and corticosterone serum concentrations were higher and estradiol lower than C. There were not differences in fetal weight between male and female per group, therefore averaged data was used; MO fetal weight was lower than C. Positive correlations were found between progesterone and corticosterone with maternal weight, and estradiol with fetal weight, while negative correlation was observed between corticosterone and fetal weight. Additionally, male umbilical cords from MO were hypermethylated in RXRα gene compared to male C group, without differences in the female groups; mRNA and protein expression of RXRα were decreased in F1 male but not in female MO compared to C. In conclusion, MO results in dysregulation of circulating steroid hormones of the obese mothers and low fetal weight in the F1, modifying DNA methylation of RXRα gene as well as RXRα mRNA and protein expression in the umbilical cord in a sex-dependent manner.